Erythroleukemia relapsing as precursor B-cell lymphoblastic leukemia - Park, Borae G; Park, Chan-Jeoung; Jang, Seongsoo; Seo, Eul Ju; Chi, Hyun-Sook; Lee, Jung-Hee (Taehan Chindan Kŏmsa Ŭihakhoe chi, 2011)
AML relapsing as ALL has rarely been reported. We describe the case of a 62-yr-old man who was diagnosed with erythroleukemia with a complex karyotype and achieved complete hematologic and cytogenetic remission after induction chemotherapy. However, 4 months after the initial diagnosis, he showed relapse with blasts showing a different morphology and immunophenotype and was diagnosed with precursor B-cell ALL. The relapsing precursor B-cell ALL presented with the same leukemic clones as the primary erythroleukemia. Cytogenetic analysis of his bone marrow (BM) at the time of the primary erythroleukemia showed complex karyotypic abnormalities, including monosomy 5 and monosomy 7. At relapse, his BM showed reemergence of these leukemic clones of complex karyotypic abnormalities with clonal switch. To our knowledge, this is the first case of a lineage switch from erythroleukemia to ALL.